Blocking of plasma kallikrein ameliorates stroke by reducing thromboinflammation. Issue 5 (13th March 2015) - Göb, Eva; Reymann, Stephan; Langhauser, Friederike; Schuhmann, Michael K.; Kraft, Peter; Thielmann, Ina; Göbel, Kerstin; Brede, Marc; Homola, György; Solymosi, László; Stoll, Guido; Geis, Christian; et al.
<x xml:space="preserve">Abstract</x> Objective Recent evidence suggests that ischemic stroke is a thromboinflammatory disease. Plasma kallikrein (PK) cleaves high–molecular‐weight kininogen to release bradykinin (BK) and is a key constituent of the proinflammatory contact‐kinin system. In addition, PK can activate coagulation factor XII, the origin of the intrinsic coagulation cascade. Thus, PK triggers 2 important pathological pathways of stroke formation, thrombosis and inflammation. Methods We investigated the consequences of PK inhibition in transient and permanent models of ischemic stroke. Results PK‐deficient mice of either sex challenged with transient middle cerebral artery occlusion developed significantly smaller brain infarctions and less severe neurological deficits compared with controls without an increase in infarct‐associated hemorrhage. This protective effect was preserved at later stages of infarctions as well as after permanent stroke. Reduced intracerebral thrombosis and improved cerebral blood flow could be identified as underlying mechanisms. Moreover, blood–brain barrier function was maintained in mice lacking PK, and the local inflammatory response was reduced. PK‐deficient mice reconstituted with PK or BK again developed brain infarctions similar to wild‐type mice. Important from a translational perspective, inhibition of PK in wild‐type mice using a PK‐specific antibody was likewise effective even when performed in a therapeutic setting up to 3 hours poststroke. Interpretation PK drives thrombus formation and inflammation via activation of the intrinsic coagulation cascade and the release of BK but appears to be dispensable for hemostasis. Hence, PK inhibition may offer a safe strategy to combat thromboembolic disorders including ischemic stroke. Ann Neurol 2015;77:784–803